Effect of birth order and spacing on the nutritional status of mother and child - Suja P Thomas (Department of Home Science, College of Agriculture, 1989)
A study of the effect of birth order and spacing on the nutritional status of mother and child was conducted among the agricultural labourers working in the instructional farm, vellayani and also among other agricultural labourers working near the Vellayani Campus.